(untitled) (Sri Lanka Journal of Indigenous Medicine (SLJIM), 2024)
Hasat-e-Mirrarah (Cholelithiasis) is a common problem with a prevalence rate of 3.2% to 15.6% has been reported from Asia. This single case study aimed to assess the efficacy of Unani compound formulations along with diet therapy in the management of Hasat-e-Mirrarah. A 34-year-old male patient visited the private clinic on 30.04.2023 with a complaint of pain in the right-side upper abdomen for 1 month. In addition to pain, he had nausea, vomiting, abdominal irritation, and indigestion. The Ultra Sound Scan of the whole abdomen confirmed that there was a fatty liver and contained multiple gall bladder calculi (the largest one 8mm). The patient was treated with Ilaj bil Dawa (Pharmaco therapy) and Ilaj bil Ghiza (Diet therapy) treatments mentioned in the Unani Medicine. Unani regimen comprised of three formulations Qurs-eKushta-e Hajrul Yahood two pills twice daily, Majoon-e-Dabeedul Ward five grams twice daily, and Ithrifal-e-Sagheer five grams twice daily were prescribed orally after meals for three months. Further, he was advised about diet. The patient’s vitals remained stable during observation and treatment, and symptoms were improved. Post-treatment Ultra Sound Scan of the whole abdomen reported as mentioned that no stone was seen in the gall bladder. It was also observed that there were no adverse drug reactions during the treatment period. This case report documented the successful medical treatment for Hasat-e Mirrarah through Unani Medicine. It concluded that the Unani regimen was effective and safe in managing Hasat-e-Mirrarah.